2022
DOI: 10.1016/j.jhsa.2021.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Diagnostic Testing for Carpal Tunnel Syndrome: A Survey of the American Society for Surgery of the Hand

Abstract: Purpose In 2016, the American Academy of Orthopaedic Surgeons (AAOS) changed the clinical practice guidelines (CPGs) for the diagnosis of carpal tunnel syndrome, relaxing the recommendation for electrodiagnostic studies (EDS) prior to offering surgery. However, it is unknown how the updated guidelines changed the practice patterns of hand surgeons.Methods A web-based multiple-choice survey was sent to the members of the American Society for Surgery of the Hand. We assessed the current diagnostic practice patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…A metallic hand goniometer was used to take the measurements. The American Society for Hand Surgery (ASSH) graded the range's result [17]. Aside from that, patients were examined before returning to work to check functional movements such as precision grip for writing, performing ADLs, use a lateral pinch, cylindrical, or spherical grip.…”
Section: Methodsmentioning
confidence: 99%
“…A metallic hand goniometer was used to take the measurements. The American Society for Hand Surgery (ASSH) graded the range's result [17]. Aside from that, patients were examined before returning to work to check functional movements such as precision grip for writing, performing ADLs, use a lateral pinch, cylindrical, or spherical grip.…”
Section: Methodsmentioning
confidence: 99%
“…Their work is important because significant practice variation can exist in initial diagnostic testing and preoperative treatments for carpal tunnel syndrome. 35 One implication of their study is that optimizing these presurgical care pathways from the diagnostic and nonsurgical management perspective will be important for reducing health care spending and promoting equitable access. To offer more equitable care, therefore, plastic surgeons should be attuned not only to disparities in postoperative outcomes, but also to costly inefficiencies in preoperative care that may disproportionately affect marginalized patient populations.…”
Section: Improving Outcomes: Equity As An Outcomementioning
confidence: 99%
“…The American Academy of Orthopaedic Surgeons (AAOS) had a clinical practice guideline 10 (CPG) on CTS in 2009 that was revised in 2016 11 to no longer recommend the routine use of EDS for the diagnosis of CTS. In the ASSH member survey, only 38% of the respondents believed that the CPGs were appropriate and 43% reported that they were not aware of the CPGs 9 .…”
Section: Carpal Tunnel Syndromementioning
confidence: 99%
“…Nevertheless, its use persists. A survey of members of the American Society for Surgery of the Hand (ASSH) (23.4% response rate) found that 26% of surgeons required EDS before they would grant an appointment and 56% of members order EDS after seeing patients if they do not already have them 9 . The American Academy of Orthopaedic Surgeons (AAOS) had a clinical practice guideline 10 (CPG) on CTS in 2009 that was revised in 2016 11 to no longer recommend the routine use of EDS for the diagnosis of CTS.…”
Section: Carpal Tunnel Syndromementioning
confidence: 99%